The Millenium of Lithuania: Two Eliminated Alternatives - Bumblauskas, Alfredas (Lietuvos istorijos studijos, 2009)
The article considers the following two events in the history of Lithuania of the 19th-20th century from the point of view of the conception of alternative history formulated by Alexander Demandt: 1) the fatal meeting with the last King and Grand Duke of the Polish-Lithuanian Commonwealth Stanislaw August Poniatowski held in Warsaw on 23 July 1792, in which the decision was taken to put up no more resistance to the Russo-Polish War - everything was determined by a seven-to-five majority of votes; 2) on 24 December 1921, the Government of Lithuania informed the League of Nations that it refused the proposed Paul Hymans' second project on Vilnius, though on the 4th of November 1921 the political elite of Lithuania spoke in support of that project. These two dates are related not only by the fact that they are reflections of the defeated historical tendencies, but also by the fact that neither of them appears in the models of the historical memory of Lithuania. Therefore, the present article is aimed at elucidating why these dates are not only excluded from the dominating models of the historical memory of Lithuania, but in essence they are not found even in historiography of Lithuania. The conclusion can be drawn that both events are treated as optics of the great national narrative that formed during the epoch of the national rebirth, which, on the basis of the "falling asleep" metaphor, refused the late history of the Grand Duchy of Lithuania, and in part regarded the integration of Vilnius into Lithuanian culture (Tumas Vaižgantas' conception of "natural Lithuanianism") with skepticism. Nonetheless, the great national narrative was influenced by a realistically triumphant political alternative, that is, the Russian factor. It influenced the ideology of the national rebirth in the second half of the 19th century, and in 1920-1924 directly contributed to the formation of the anti-Polish ideology, as well as the evaluation of the year 1921 from the perspective of the 12th of July 1920 - the 10th of October 1939, that is, from the perspective of returning Vilnius to Lithuania from Stalin's Russia. Hence, a typological, and partly genetic, connection between 1791, 1921, and the modern anti-May and anti-humanistic tendencies both in political and historical culture is discovered. At the same time, attention is drawn to the fact that rejection of both the Constitution of Third May and Paul Hymans' second project had a tragic outcome - the historical alternatives that triumphed led to the destruction of both the Grand Duchy of Lithuania in 1795 and the Republic of Lithuania in 1940.
Keywords: -